Association of Serum Vitamin D Levels with Disease Severity in Chronic Plaque Psoriasis and Coexisting Obstructive Pulmonary Disease - Noor-Ul-Ain Malik Sohail, Minahil Sarfraz Ahmad Basirat, Syed Azhar Hussain Zaidi Aisha Malik, Naima Khalid (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Serum vitamin D deficiency has been implicated in both chronic plaque psoriasis (CPP) severityand chronic obstructive pulmonary disease (COPD) progression. This mixed-design studycomprised a meta-analysis of observational studies quantifying associations between serum25-hydroxyvitamin D [25(OH)D] and disease severity